PELATIHAN DAN PENDAMPINGAN PEMBUATAN RANCANG BANGUN UNDERWATER LED UNTUK BAGAN PERAHU DI LHOK LAYEUN, ACEH BESAR - Fuah, Ricky Winrison; Agustina, Imelda; Halim, Raji Ufranal; Rusminda, Heni; Gurki, Yeni Safitri; Riswan, M (Universitas Mataram, 2025)
Lift-net fishermen in Gampong Lhok Layeun, Leupung Sub-district, Aceh Besar District, still use mercury lamps which are energy-intensive, require high operational costs, and are less effective in attracting fish. This condition leads to low profits for fishermen. To address this problem, a community service program was conducted in the form of training and assistance in the development of underwater light emitting diode (LED) as an alternative technology that is more energy-efficient and effective. This activity aimed to enhance fishermen’s capacity in mastering appropriate technology and reducing fishing operational costs. The program was held on August 23–24, 2025, at the Layeun Village Office Hall, involving 15 fishermen, three lecturers, and three students from Universitas Syiah Kuala. The implementation method applied an applicative and participatory approach through several stages: preparation, training, hands-on practice, and evaluation. Participants received materials on the concept and advantages of underwater LED, followed by direct assistance in assembling the devices and conducting simple trials. The results showed an increase in fishermen’s understanding of the differences between lighting technologies as well as their ability to assemble underwater LED devices independently. Fishermen expressed their readiness to adopt this technology because it is more energy-efficient, reduces operational costs, and has the potential to increase fish catches. In conclusion, this program successfully improved fishermen’s knowledge and skills in utilizing underwater LED technology, which can serve as an alternative solution to enhance the welfare of coastal communities and support sustainable fisheries resource management.